2015
DOI: 10.1038/nature16441
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional preservation of tiny embryos documents seed dormancy in early angiosperms

Abstract: The rapid diversification of angiosperms through the Early Cretaceous, between about 130 and 100 million years ago initiated fundamental changes in the composition of terrestrial vegetation and is increasingly well-understood based on a wealth of palaeobotanical discoveries over the last four decades [1][2][3][4][5] , and their integration with improved knowledge of living angiosperms 3,6 . Prevailing hypotheses, based on evidence from both living and fossil plants, emphasize that the earliest angiosperms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…This is in line with the ecophysiological analyses of extant and fossil plants, which conclude that herbaceous habit may well have been adopted by early angiosperms (Stebbins, 1981;Taylor and Hickey, 1990, 1992, 1996Carlquist, 1996;Royer et al, 2010). This conclusion has been favored by recent studies on Early Cretaceous plants (Jud, 2015;Friis et al, 2015). Juraherba unequivocally confirms that early angiosperms have already adopted this strategy at least back to the Middle Jurassic (Figs.…”
Section: Herbaceous Habitsupporting
confidence: 85%
“…This is in line with the ecophysiological analyses of extant and fossil plants, which conclude that herbaceous habit may well have been adopted by early angiosperms (Stebbins, 1981;Taylor and Hickey, 1990, 1992, 1996Carlquist, 1996;Royer et al, 2010). This conclusion has been favored by recent studies on Early Cretaceous plants (Jud, 2015;Friis et al, 2015). Juraherba unequivocally confirms that early angiosperms have already adopted this strategy at least back to the Middle Jurassic (Figs.…”
Section: Herbaceous Habitsupporting
confidence: 85%
“…Recently Friis et al [1] also reported nuclei in exquisite Early Cretaceous fossil seeds. Although their main conclusion that herbs are among early angiosperms is an old idea dated back to 1960s [1] and is supported by recent discovery of Jurassic herbaceous plant [6], their claim of nuclei deserves further scrutiny. Here, to shed more light on this issue, some plant mesofossils from the AlbianCenomanian (Cretaceous) of Kansas, USA, were studied using LM, SEM and TEM [7] [8].…”
Section: Introductionmentioning
confidence: 97%
“…Some researchers have published excellent papers regarding this aspect [2]- [5]. Recently Friis et al [1] also reported nuclei in exquisite Early Cretaceous fossil seeds. Although their main conclusion that herbs are among early angiosperms is an old idea dated back to 1960s [1] and is supported by recent discovery of Jurassic herbaceous plant [6], their claim of nuclei deserves further scrutiny.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesofossil assemblages are rich in angiosperm flowers and inflorescences as well as isolated fruits, seeds and stamens of angiosperms, in addition to a diversity of seeds related to the Bennettitales-Erdtmanithecales-Gnetales complex, conifer seeds and twigs of Cheirolepidiaceae as well as many fern fragments and megaspores (e.g. Friis et al 1994Friis et al , 2009Friis et al , 2010Friis et al , 2014bFriis et al , 2015aFriis et al , 2015bFriis & Pedersen 2014).…”
Section: Methodsmentioning
confidence: 99%